Was Mickiewicz a great translator? Adam Mickiewicz as a translator of German-language texts into Polish - Siwek, Karolina (Free your mind: Reflections on language, literature and culture, 2022)
The figure of Adam Mickiewicz as a poet, national bard, political activist Sand founder of the Philomath Society is well known. The aim of the paper is to present Mickiewicz in a lesser-known role of a literary translator translating from German into Polish. Thus, an attempt will be made to answer the question about the reasons for Mickiewicz's translation activity and the ways in which these translations were perceived by his literary contemporaries. In order to do so, an analysis will be made of the Polish poet's translation output, critical statements and self-commentaries of Mickiewicz himself. The analysis of the material allows us to conclude that Mickiewicz "was a great translator", but that translation played an "auxiliary" role for him. In particular, translations of the works of Schiller, and later Goethe, were reflected in Mickiewicz's original work, but also contributed to the development of the Philomat Society. Translations from German were a source of inspiration and new aesthetic trends unknown and unpracticed in Polish literature at the time, which in effect opened the gates to European Romanticism. Mickiewicz's translations served as a means of acquiring ideas and knowledge about other literatures, and he himself, despite his successful works, did not identify with the role of literary translator.